The necessary conduct: Exploratory multiregional clinical trials in East Asia. Issue 6 (16th August 2021) - Jeon, Inseung; Kim, Yu Kyong; Song, Ildae; Yoon, Deok Yong; Huh, Ki Young; Jin, Xuanyou; Yu, Kyung‐Sang; Lee, SeungHwan; Kumagai, Yuji; Jang, In‐Jin
Abstract: Various studies have highlighted the importance of ethnic differences. The consideration of ethnic differences in the field of individualized pharmacotherapy is imperative. Therefore, various organizations and networks across countries should aim to conduct multicountry and multiregional clinical trials (MRCTs). If there is solid evidence available to evaluate the existence of ethnic differences between the same regional areas, it will lead to an increase in the efficiency of drug development. The purpose of this paper was to compare the approval dosing regimen among four Asian countries (Korea, Japan, China, and Taiwan) and elucidate the readiness and current status of the implementation of the International Conference on Harmonization (ICH) E17 guidelines on MRCTs. Reducing unnecessary clinical trials via multinational clinical trials in East Asian countries is also suggested. The approved dosing regimens for some drugs in the four Asian countries were similar; however, some differences might be caused by differences in legislation, even though there were no ethnic differences. This indicates that there are several roles to be expected of the Asia Clinical Pharmacology study network for exploratory MRCTs, which would lead to the accumulation of evidence for MRCTs, ultimately accelerating the efficiency of drug development in East Asian countries. The exposure of the new treatment to the necessary patients through collaborative research coordination and simultaneous multinational subject recruitment would serve its role in providing East Asia with specific personalized medicine with a high treatment success rate.